Analisis Perhitungan, Pencatatan Dan Pelaporan Pajak Pertambahan Nilai - Irfan Fatoni Fatoni; Lilik Hardiana Hardiana; Gunarianto Gunarianto Gunarianto; Indah Dewi Nurhayati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Taxes are one of the main sources of income for the State of Indonesia, so it is mandatory for every individual and every company to make tax payments in accordance with the current laws and regulations. PT. Jaring Abadi Retalindo is a company that has fulfilled this responsibility and is considered successful. This study examines the methodology behind PT. Jaring Abadi Retailindo Eternal Net tax calculation, recording and reporting system. The methodology used includes descriptive and qualitative approaches, and the data comes from PT. Jaring Abadi Retailindo throughout 2020 and 2021. Tax invoices and monthly tax deposit reports used are data. In line with Law no. 42 of 2009, the purpose of this study is to evaluate how the application of VAT can result in an overpayment or underpayment of taxes, particularly in relation to the calculation, recording, and reporting of Input Tax and Output Tax. The research findings allow one to draw the conclusion that PT. Jaring Abadi Retailindo complies with the applicable laws and regulations, both in calculating and recording taxes, as well as reporting that must be submitted.